2002
DOI: 10.1128/aac.46.5.1375-1380.2002
|View full text |Cite
|
Sign up to set email alerts
|

PEPT1-Mediated Cefixime Uptake into Human Intestinal Epithelial Cells Is Increased by Ca 2+ Channel Blockers

Abstract: The ␤-lactam antibiotic group encompasses the penicillins, cephalosporins, carbapenems, and monobactams (13). The high intestinal absorption rates of orally active ␤-lactams are mainly explained by the fact that they serve as substrates for the intestinal peptide transporter PEPT1 (10). PEPT1 is located in the apical membranes of intestinal epithelial cells (23) and the Caco-2 human intestinal epithelial cell line (39). The peptide transporter translocates di-and tripeptides (17, 33) as well as a variety of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
3
31
0
1
Order By: Relevance
“…The issue of A-23187 access to the membranes of mature Caco-2 cells has been addressed by others (21,25). Direct effects of A-23187 on Ca 2ϩ flux and indirect effects of A-23187 on signaling responses to changes in intracellular Ca 2ϩ concentration were maintained in differentiated Caco-2 cells grown on permeable supports identical to our culture conditions.…”
Section: Discussionmentioning
confidence: 80%
“…The issue of A-23187 access to the membranes of mature Caco-2 cells has been addressed by others (21,25). Direct effects of A-23187 on Ca 2ϩ flux and indirect effects of A-23187 on signaling responses to changes in intracellular Ca 2ϩ concentration were maintained in differentiated Caco-2 cells grown on permeable supports identical to our culture conditions.…”
Section: Discussionmentioning
confidence: 80%
“…As PEPT1 transport activity also depends on the transmembrane proton gradient, which is mainly generated by the apical Na/H exchanger, any manoeuvres that alter pH gradients and membrane potential secondarily affect PEPT1 activity [67]. In Caco-2 cells, PEPT1 expression is reduced by treatment with thyroid hormone [1] whereas Ca 2+ channel blockers, by decreasing intracellular calcium, increase PEPT1 activity acutely whereas elevating intracellular free calcium decreases the maximal transport activity [72]. A very interesting adaptation is observed in patients with short bowel syndrome whose colonic epithelial cells express substantial quantities of PEPT1 protein, which is normally not found in the human colon or present in only very low levels [77].…”
Section: Regulation Of Transport Activitymentioning
confidence: 97%
“…It has been reported that PEPT1 activity is regulated by several intracellular factors, such as the activity of protein kinaseC, 34) cAMP level, 35) or Ca 2ϩ concentration. 24) In addition to these factors, an Na ϩ /H ϩ exchanger is also shown to be a factor determining PEPT1 activity. 36) That is, the exchanger is demonstrated to regulate the proton gradient across the cellular membrane, which PEPT1 requires as a driving force for its H ϩ /peptide co-transporting function.…”
Section: Discussionmentioning
confidence: 99%
“…23) In addition to the paracellular pathway of the intestinal drug absorption processes, capsaicin may affect the transcellular pathway of the process, since the intracellular Ca 2ϩ concentration is related to the drug transporting activity of various transporters including H ϩ /peptide co-transporter 1 (PEPT1). 24) It is therefore suggested with these findings and considerations that capsaicin has an impact on the intestinal drug absorption processes. However, little is known about the effect of capsaicin on intestinal drug absorption.…”
mentioning
confidence: 99%